ChemInform Abstract: Molten Salt Synthesis of Nano‐Sized Li4Ti5O12 Doped with Fe2O3 for Use as Anode Material in the Lithium‐Ion Battery. Issue 11 (March 2015) - Guo, Qingjun; Li, Shiyan; Wang, Heng; Gao, Yuan; Li, Bing
Abstract Single‐phase Li4Ti5‐xFexO12 (x = 0, 0.1, 0.2, 0.3) are prepared from LiOH, TiO2, and Fe2O3 in LiCl‐KCl molten salt (corundum crucible, 800 °C, 4 h).